2022
DOI: 10.3389/fphys.2022.1023589
|View full text |Cite
|
Sign up to set email alerts
|

Comparing algorithms for assessing upper limb use with inertial measurement units

Abstract: The various existing measures to quantify upper limb use from wrist-worn inertial measurement units can be grouped into three categories: 1) Thresholded activity counting, 2) Gross movement score and 3) machine learning. However, there is currently no direct comparison of all these measures on a single dataset. While machine learning is a promising approach to detecting upper limb use, there is currently no knowledge of the information used by machine learning measures and the data-related factors that influen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…For example, automatic detection of vestibular gait is possible with good accuracy if data is restricted to a specific task [ 51 ]. For upper extremity tasks, several studies have found that wrist-worn IMUs and Random Forest Classifiers are superior to other processing methods for detecting functional arm use in stroke [ 52 , 53 ]. Another group is working to provide a more detailed description of the upper extremity function, by first identifying five primitives of the upper extremity function: reaching, transporting, repositioning, stabilizing, and idling [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, automatic detection of vestibular gait is possible with good accuracy if data is restricted to a specific task [ 51 ]. For upper extremity tasks, several studies have found that wrist-worn IMUs and Random Forest Classifiers are superior to other processing methods for detecting functional arm use in stroke [ 52 , 53 ]. Another group is working to provide a more detailed description of the upper extremity function, by first identifying five primitives of the upper extremity function: reaching, transporting, repositioning, stabilizing, and idling [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several measures have been proposed in the literature to detect UL use from a single IMU [5, 7, 8, 10]. These measures can be broadly categorized into traditional [5, 10, 11] and machine learning(ML)-based measures [6,10]; we use the terms measure, model, and algorithm interchangeably in the rest of the manuscript. The traditional measures are simple, hand-crafted algorithms with pre-specified parameter values that use specific signal features to detect UL use.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, ML-based measures are algorithms trained on a set of labeled data to detect UL use from IMUs. Random forests, support vector machines, and multilayer perceptrons have been reported previously [6, 10], with the random forests [6, 10] offering the best performance to date. Additionally, intra-subject (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations